Penegakan Hukum Tindak Pidana Pencucian Uang dari Hasil Tindak Pidana Korupsi di Indonesia - Fatikh Ilhamul Alam; M. Muhammad Bangsu (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study is to discuss and analyze the procedures for money laundering committed by perpetrators of corruption as well as discuss and analyze the law enforcement of money laundering from the proceeds of corruption in terms of Law of the Republic of Indonesia Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering. This research is included in juridical research. The results showed that the procedure for money laundering carried out by perpetrators of corruption was carried out in three stages. First, placement is the separation of the wealth resulting from crime from the source of crime. Second, separation or layering is the transfer of funds from several accounts or certain locations to other places through a series of complex transactions and designed to disguise and eliminate traces of the source of these funds. Third, integration, namely using assets resulting from criminal acts that have been placed and / or layered (layering) that appear as legitimate assets, for halal business activities or refinance criminal activities. The results also show that law enforcement of money laundering from the proceeds of corruption in terms of Law of the Republic of Indonesia Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering shows that the process of money laundering does not have to wait for a criminal verdict on the original crime (predicate crime) so that it is sufficient to suspect that the wealth comes from the proceeds of criminal acts then criminal Money laundering can be applied as long as all criminal elements and criminal procedural processes have been fulfilled.